Classics. The results 3 years later and the technic of alloplasty of the muscles in scoliosis - Adam Gruca (Chirurgia Narządów Ruchu i Ortopedia Polska)
This abstract was not part of the original article by Adam Gruca and was added by the Editors of Chirurgia Narządów Ruchu i Ortopedia Polska – Polish Orthopaedics. The author of the article presented three-year results of the treatment of 3 series of patients treated for scoliosis of the 1st, 2nd and 3rd degree with the technique of so-called muscle alloplasty. In 1st degree scoliosis, posterior alloplasty with spring attachment on the transverse and spinous processes causes complete or almost complete correction of the curvature in all cases. The results are stable. In lumbar scoliosis, iliolumbar alloplasty is preferred over intertransverse alloplasty. In 2nd and 3rd degree scoliosis, posterior alloplasty causes partial correction of the curvature in 70-80% of cases (second series), promoting rotation of the apical vertebrae. Anterior interpedicular or iliolumbar alloplasty causes a reduction of the rib prominence and vertebral rotation; curvature is reduced in all cases. Correction was 25% better than in the case of posterior alloplasty. Anterior interpedicular alloplasty is recommended in moderate and severe scoliosis, especially in pre-pubertal children. In severe prepubertal and very severe postpubertal scoliosis (curvatures greater than 90), wedge resection of the apical vertebral bodies and correction of the curvature followed by application of a cast and secondary anterior alloplasty, gives promising results.